141 Challenges to home-based COVID testing in rural Latino and Native American communities. (April 2022) - Gregor, Charlie; Webber, Eliza; Hassell, Laurie; Thompson, Matthew; Drain, Paul; Ko, Linda; Dupuis, Virgil; Garza, Lorenzo; Lambert, Allison; Bishop, Sonia; Warne, Teresa
Abstract : OBJECTIVES/GOALS: Test the effects of a community health worker supported model to deliver home-based COVID-19 testing in the Yakima Valley (Washington) and Flathead Reservation (Montana) METHODS/STUDY POPULATION: A pragmatic, randomized controlled clinical trial evaluating the effects of a community health worker supported model to deliver home-based COVID-19 testing in the Yakima Valley (Washington) and Flathead Reservation (Montana) vs. a modified direct-to-consumer. 400 participants will be enrolled, 200 from each community. Outcomes include comparing the number of completed testing kits as well as the number of testing kits with successful (detected vs not-detected) results. RESULTS/ANTICIPATED RESULTS: The poster presents preliminary results from 191 participants, blinded to study assignment. To date, 53% of enrolled participants returned a sample for testing and 39% received a usable (detected or not-detected) result. Our populations experienced a high-rate (16%) of sample errors, required 28 replacement kits and had 20 participants randomized to the control arm receive the intervention to ensure participants received testing during the pandemic. DISCUSSION/SIGNIFICANCE: Home-based testing models are build for those who are proficient in verbal and written English, have high tech. literacy and continuous access to internet. For home-based testing to have similar success rates as white Americans, cultural and demographic differences and disparities will need to be accounted for in development and implementation.